EVALUATION OF SOME COMPONENTS OF CHOICE MAKING. Issue 2 (20th May 2013) - Sellers, Tyra P.; Bloom, Sarah E.; Samaha, Andrew L.; Dayton, Elizabeth; Lambert, Joseph M.; Keyl‐Austin, Alice A.
Abstract Providing access to choice‐making opportunities is a useful addition to behavioral interventions, although the critical features of choice making may differ greatly across individuals. In this study, results of an initial 3‐choice concurrent‐operants preference assessment with 4 subjects with autism spectrum disorder suggested that 2 subjects preferred the choice‐making condition and participated in subsequent assessments to examine the potential influences of reinforcer variability and differential access to high‐preference reinforcers on their preferences for choice making. Two other subjects did not prefer the choice‐making condition and participated in subsequent assessments to explore conditions under which they might prefer choice‐making opportunities. Results suggested that a wide range of variables influenced preference for choice‐making conditions.